(untitled) (Annals of Medical Research, 2022)
Aim: Laparoscopic ventral mesh rectopexy (LVMR) has gained popularity in the treatment of obstructed defecation syndrome (ODS) related morphological disorders of the pelvic floor. The aim of this study is to investigate the effectiveness, safety and early functional results of the LVMR, especially in ODS-related disorders. Materials and Methods: Data of patients who underwent LVMR between May 2019 and December 2020 were retrospectively analyzed. Demographic characteristics, comorbid diseases, presence of previous abdominal surgery, proctological examination findings, dynamic magnetic resonance defecography results, anal manometer results, early and late complications, postoperative length of hospital stay of patients were recorded. Wexner Incontinence Score (WIS) and Wexner Constipation Score (WCS) were used in the preoperative and postoperative third month to evaluate the functional recoveries of patients. Results: Of 14 patients, one was man (7.1%) and 13 were women (92.9%). The mean age of the patients was 43.71 ± 11.72 years (range 24-61). Mean length of follow-up was 11.14 ± 4.52 months (range 4-19). Three (21.43%) of the patients had external rectal prolapse and 11 (78.57%) had ODS-related rectocele. In these 11 patients with ODS, the mean preoperative and postoperative WCS were 15.81 ± 3.68 (range 11-24) and 7.45 ± 3.24 (range 4-14), respectively, indicating a statistically significant difference (p< 0.001). Conclusion: LVMR is a safe procedure if performed with a selective approach after a thorough preoperative evaluation in ODS patients and a remarkable level of functional recovery can be achieved in these patients, particularly in the postoperative early period.